The complexity of approximating the matching polynomial in the complex plane - Bezakova, I; Galanis, A; Goldberg, LA; Stefankovic, D (Association for Computing Machinery, 2021)
We study the problem of approximating the value of the matching polynomial on graphs with edge parameter γ, where γ takes arbitrary values in the complex plane.